Postnatal exposure to finasteride causes different effects on the prostate of male and female gerbils - Maldarine, Juliana S.; Sanches, Bruno D. A.; Santos, Vitória A. [UNESP]; Cabral, Ágata S. [UNESP]; Lima, Maria L. D. [UNESP]; Bedolo, Carolina M. [UNESP]; Calmon, Marília F. [UNESP]; Rahal, Paula [UNESP]; Góes, Rejane M. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastião R. [UNESP] (Wiley, 2020)
The development and maintenance of prostate function depend on a fine balance between oestrogen and androgen levels. Finasteride inhibits 5α-reductase, which is responsible for the conversion of testosterone into its most active form, dihydrotestosterone. Enzymes that metabolize these hormones have a highly relevant role in both the normal prostate metabolism and in the occurrence of pathological conditions. There are few studies on the impact of finasteride on male prostate development and fewer studies on the female prostate and possible intersexual differences. Therefore, we treated male and female gerbils from 7 to 14 days in postnatal life with a high dose of finasteride (500 μg/kg/day); the prostate complexes were then removed and submitted to immunohistochemistry, immunofluorescence and three-dimensional reconstruction. In addition, hormonal serum dosages were administered. Treatment with finasteride resulted in an increased thickness of the periductal smooth musculature in the prostate of both male and female gerbils, such as well as a reduction in the thickness of developing prostate alveoli in both sexes. In addition, intersexual differences were observed as increased epithelial proliferation and decreases in the number of developing alveoli in females. Together, the data indicate that postnatal exposure to finasteride causes greater changes in the female gerbil prostate than in the male.
Keywords: androgen receptor; branching morphogenesis; developmental exposure; female prostate; finasteride; gerbil